The relationship between self-skills and efforts among traditional fishermen in Kuala Perlis, Malaysia - Ibrahim, Sharifah Sofiah ‘Atiqah Syed; Ismail, Hamidi; Hussain, Tuan Pah Rokiah Syed (Nurture, 2023)
Purpose: This study aims to analyze the relationship between aspects of personal life-skills values and the efforts of traditional fishing families in Kuala Perlis in dealing with poverty. Design/Methodology/Approach: The sample consisted of 333 owners of households of traditional fishermen in Kuala Perlis, Malaysia. A Pearson correlation test was used to achieve the research objectives. Findings: The findings indicated that the fishermen’s efforts were good in dealing with poverty. However, the local fishermen of Kuala Perlis still live in poverty. Conclusion: According to the study, fishermen’s poverty was probably caused by the need for continual improvement in various life skills. This would help them deal with poverty more effectively. Research Implications: The implication of this study was that traditional fishermen should improve their life skills in order to reduce the poverty they experience. This was proven by Pearson’s correlation analysis which showed a positive relationship between the constructs. Practical Implications: Traditional fishermen need to strengthen themselves with knowledge related to the value of personal skills in order to deal with family poverty. Contribution to Literature: In the context of literature, this research contributes to the study of poverty among traditional fishermen especially in the aspect of self-skills.